Sons de ecolocalização e preferência de habitat de morcegos insetívoros aéreos do Estado do Espírito Santo - Almeida, Márcio Henrique (2016)
This work is dividedin two parts. In the first chapter we evaluated the importance ofpreserved areas for aerial insectivorous bat activity within an urban zone. Severalstudiespoint out that urbanizationhasanegativeimpact onbats. However, urbanization’s impactmight differ between bats that forage in open space and those that forage in cluttered space,with the latter usually persisting only in well preserved areas,suchas parks and naturalreserves. Our objectivewastocompare aerial insectivorous bat activity amonggreen areaswith different sizes andurban sites distant from vegetation fragments in greaterVitóriaregion, Espírito Santo State, Brazil. For this purpose, we monitored bat activity with anultrasound detector during two years in three habitats: large green areas ( > 30ha), small greenareas (< 5 ha) and non-green urban areas. The Largegreen area showed the greatestbatactivity followed by the small green area and the non-green urban area. The large green areashowed a largerincreasein cluttered space forager activity than in open space forger activitywhen compared to the other habitats, whereas the small green area showed a largerincreaseinopen space bat activity when compared to the urban area. Therefore, in Great Vitória region,even small parks are important for bat fauna conservation, whereas bats that forage incluttered space,suchasMyotis sp., depend on large preserved areas to persist. In the secondchapter, in order to create a reference data base for recognition ofbats in theMolossusgenus,whose vocalizations were regularly recorded in GreaterVitória, we compared theecholocation calls of three species of this genus:M. molossus,M. rufuseM. coibensis.M.rufusshowed the lowest call frequency among the three species. This pattern can be explainedby the fact thatM. rufusarenotably larger than the other species. However, pulse duration didnot differ betweenM. rufusandM. coibensisand it was longer in these species than inM.molossuswhen we compared quasi-constant frequency calls and shorter when we comparedfrequency modulated calls. Therefore, other factors, notonlybody size,such as flight orforagingbehavior must explain the pattern that we found for temporal parameters in thesespecies